Complete excision and soft tissue augmentation after recurrence of a peripheral ossifying fibroma as a pyogenic granuloma: A case report - Ramtin Chitsazha; Masoumeh Faramarzi; Negin Firouzi (Tabriz University of Medical Sciences, 2020)
Reactive lesions of soft tissue are common oral lesions that are usually non-neoplastic growths without pain; however, they can interfere with oral hygiene and plaque control, and if present in the anterior segment, they can cause esthetics problems. In this case, there was a reactive lesion at the gingiva of the left maxillary central incisor area. The particular consideration about this case was the recurrence of a peripheral ossifying fibroma as a pyogenic granuloma, indicating the association between reactive gingival lesions. The history of several recurrences due to incomplete removal shows the importance of complete excision for preventing recurrence. Therefore, the lesion was completely excised, and the mucogingival defect was successfully augmented with periodontal plastic surgery.